The ivory tower and beyond: Bradford University at the heart of its communities - Pearce, Jenny; Pearson, Martin; Cameron, Sam (University of Bradford, 2007)
REAP stands for Reciprocity, Externalities, Access and Partnership. It is about how a University can work with communities for mutual benefit as well as the enhancement of the city, town or district in which the University is located
A inspiré l'outil d'auto-évaluation de l'engagement des communautés de l'Université de Calgary.
Keywords: Libre accès; UK; Université